2003
DOI: 10.2320/matertrans.44.2141
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Mechanical Properties of Mg<SUB>65</SUB>Cu<SUB>15</SUB>Ag<SUB>5</SUB>Pd<SUB>5</SUB>Gd<SUB>10</SUB> Bulk Metallic Glass

Abstract: The effect of partial substitution of Cu for Ag and Pd on the glass forming ability of Mg 65 Cu 25 Gd 10 alloy has been studied. Mg 65 Cu 15 Ag 5 Pd 5 Gd 10 bulk metallic glass with diameter of at least 10 mm can successfully be fabricated by conventional Cu-mold casting method in air atmosphere. The critical cooling rate for glass formation is estimated to be $0:7 K/s. The compressive fracture strength and fracture elongation of the Mg 65 Cu 15 Ag 5 Pd 5 Gd 10 bulk metallic glass are 817 MPa and 1.6% respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In fact, in the extreme case one could attain amorphous Mg alloys at certain multicomponent compositions under chill-casting (copper mold casting) conditions, forming the so-called bulk metallic glasses (BMGs). [4][5][6][7][8][9][10][11][12][13] The Mg-based BMGs can have a strength higher than all the crystalline Mg-alloys mentioned above. Unfortunately, BMGs plastically deform by the formation of highly localized shear bands that lead to catastrophic failure under unconstrained conditions, without much macroscopic plasticity.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, in the extreme case one could attain amorphous Mg alloys at certain multicomponent compositions under chill-casting (copper mold casting) conditions, forming the so-called bulk metallic glasses (BMGs). [4][5][6][7][8][9][10][11][12][13] The Mg-based BMGs can have a strength higher than all the crystalline Mg-alloys mentioned above. Unfortunately, BMGs plastically deform by the formation of highly localized shear bands that lead to catastrophic failure under unconstrained conditions, without much macroscopic plasticity.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, Mg 65 Cu 25 Gd 10 with higher glass-forming ability has also been reported and its glass rod with diameter of at least 8 mm can be fabricated by the copper mold casting method [13] . Furthermore, based on Mg-Cu-Gd ternary system, the quaternary Mg-Cu-Ni-Gd alloy [14] and a quinary Mg-Cu-Ag-Pd-Gd alloy [15] have been developed. A bulk glassy alloy with a diameter of 10 mm was produced for Mg 65 Cu 15 Ag 5 Pd 5 Gd 10 by the copper mold casting method.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that Mg 65 Cu 25 Gd 10 alloy [7] exhibits a significantly improved GFA so that metallic glass rods with diameter of 8 mm were obtained by copper mold casting. Moreover, based on Mg 65 Cu 25 Gd 10 , a series of new Mg-based amorphous alloys with higher GFA have been developed [8][9][10][11][12][13][14] . So Mg 65 Cu 25 Gd 10 has become the foundation for studying other Mg-based metallic glasses, however, the understanding of Mg 65 Cu 25 Gd 10 is very limited.…”
Section: Introductionmentioning
confidence: 99%